AB0029 INHIBITION OF EFFECTOR B CELLS BY IBRUTINIB IN SYSTEMIC SCLEROSIS. (2nd June 2020) - Einhaus, J.; Pecher, A. C.; Asteriti, E.; Schmid, H.; Secker, K. A.; Duerr-Stoerzer, S.; Keppeler, H.; Klein, R.; Schneidawind, C.; Henes, J.; Schneidawind, D.
Abstract : Background: Systemic sclerosis (SSc) is a connective tissue disease with significant morbidity and mortality. Effective treatment is still missing, and clinical control of the disease remains challenging. In particular, the development of pulmonary and cardiac fibrosis and pulmonary hypertension are severe complications responsible for excessive mortality. Currently available treatment strategies – besides aggressive autologous stem cell transplantation which is an option only for selected patients – only alleviate symptoms and slow disease progression. Previous attempts of immunomodulating therapies addressing B cell pathology like rituximab and tocilizumab in SSc showed mixed efficacy 1, 2 Objectives: Here, we investigated the therapeutic potential of ibrutinib, a Bruton's tyrosine kinase (BTK) inhibitor used in B cell malignancies, to alter B cell pathology in SSc in an in vitro model of autoimmunity. Methods: PBMCs and sorted B cells of 24 patients with SSc were used for functional testing after stimulation with hypomethylated DNA fragments (CpG) to induce an innate immune response. The effects of ibrutinib on cytokine production, autoantibody release and activation of the transcription factor NFκB were evaluated via multiplex cytokine assay, ELISA and flow cytometry. Results: Ibrutinib was able to reduce the production of the profibrotic hallmark cytokines IL-6 and TNF-α, which are mainly released by the effector B cell population, in response to TLR9-stimulation. Importantly, small doses of ibrutinib (0.1 µM) preserved the production of immunoregulatory IL-10 and IFN-γ while effectively inhibiting the cardinal cytokines of hyperactivated profibrotic effector B cells in SSc. Intracellular cytokine staining of IL-6 in B cell subsets further endorsed the potential of ibrutinib to inhibit B cells in a subset-specific manner, reducing IL-6 + naïve B cells significantly but not IL-6 + memory B cells. The subset specificity was abolished when high doses of ibrutinib (10 µM) were applied. In a flow cytometry analysis of phosphorylated NFκB, an important transcription factor in the induction of innate immune responses in B cells, significantly less activation was observed with ibrutinib treatment (0.1 µM). Higher doses of ibrutinib were unable to further reduce the abundance of pNFκB. Conclusion: Our data could pave the avenue for a clinical application of ibrutinib for patients with SSc as a novel treatment option for the underlying pathogenetic immune imbalance contributing to disease onset and progression. References: [1]Khanna, D. et al. Efficacy and Safety of Tocilizumab for the Treatment of Systemic Sclerosis: Results from a Phase 3 Randomized Controlled Trial [abstract]. Arthritis Rheumatol. 2018; 70 (suppl 10). [2]Jordan, S. et al. Effects and safety of rituximab in systemic sclerosis: an analysis from the European Scleroderma Trial and Research (EUSTAR) group. Ann. Rheum. Dis. 74, 1188–1194 (2015). Disclosure of Interests: Jakob Einhaus: None declared, Ann-Christin Pecher: None declared, Elisa Asteriti: None declared, Hannes Schmid: None declared, Kathy-Ann Secker: None declared, Silke Duerr-Stoerzer: None declared, Hildegard Keppeler: None declared, Reinhild Klein: None declared, Corina Schneidawind: None declared, Jörg Henes Grant/research support from: Novartis, Roche-Chugai, Consultant of: Novartis, Roche, Celgene, Pfizer, Abbvie, Sanofi, Boehringer-Ingelheim, , Dominik Schneidawind: None declared